Quantifying Aquatic Carbon and Nitrogen Dynamics and Greenhouse Gas Mitigation Potential in Riparian Agroforestry Zones - Hundal, Harkirat (University of Waterloo, 2023)
Agricultural intensification in Canada has led to a loss of riparian areas, which has resulted in the degradation of freshwater aquatic ecosystems due to an increasing amount of fertilizer and nutrients being introduced from the upland vegetation. Rehabilitation/restoration of the riparian areas has been shown to minimize these effects. The main objective of my research study is to quantify the carbon (C) and nitrogen (N) dynamics in the aquatic component of the Riparian Agroforestry Systems (RAFS) with varied vegetation located along Washington Creek, Ontario, Canada. The four different treatments studied had the following vegetation types: rehabilitated forest (RH), undisturbed natural forest dominated by deciduous vegetation (UNF-D), herbaceous vegetation (HB), or undisturbed natural forest dominated by coniferous vegetation (UNF-C). No significant spatial differences were found in the Carbon di-oxide concentrations of the RAFS. Among the four riparian treatments, UNF-C recorded significantly lower (p = 0.003) and HB recorded significantly higher (p = 0.002) Methane concentration. Stream DOC concentrations were different among the treatments, with UNF-C reporting significantly lower (p = 0.035) concentrations as compared to the other treatments. Sediment OC was the highest in the RH treatment, and lowest in the HB treatment. Among the four riparian treatments, HB recorded significantly lower (p = 0.024) and UNF-C recorded significantly higher (p = 0.000) Nitrous oxide concentration. Riparian zone averages for TN concentration show that on average UNF-C recorded significantly higher (p = 0.000) values compared to the other treatments, where other N species like ammonium and nitrate were not significantly different amongst treatments. Mean sediment ammonium concentrations were the highest in the RH treatment, along with stream TN. Stream nitrate concentrations were similar among the treatments. Even though the terrestrial morphology of the RH and UNF-D riparian zone were different, including vegetation type and buffer width, but the aquatic component morphology for parameters like discharge, pH, DO, water temperature were similar. Furthermore, the chemical composition of the water in these riparian streams, that is, the GHG concentrations and other C and N species, were insignificantly different. This finding is the highlight of this study. Despite the differences in the terrestrial component, RH, which is a shorter and younger rehabilitated buffer, is just as effective at improving the water quality as is a 100-year-old and much wider forested buffer UNF-D. Therefore, implementing RH buffers at a BMP could potentially lead to water quality improvement in an agricultural landscape.